Pemberdayaan komunitas purna Pekerja Migran Indonesia melalui organisasi berbasis komunitas Forum Warga Buruh Migran - Rahmat Saleh; Ricardi S. Adnan; Aswatini Raharto (Research Centre for Population, National Research and Innovation Agency (BRIN), 2022)
Nowadays, Community-Based Organisation (CBO) has been admitted as a more successful activity to empower the community than other organisations, such as Non-Governmental Organisation (NGO). This article aims to emphasise how activism of the Forum of Indonesian Migrant Workers or the Forum Warga Buruh Migran (FWBM), as a CBO initiated by Nahdlatul Ulama (NU) at the grassroots level, works to empower ex-Indonesian migrant workers and their families in their areas of origin. This article used the qualitative methodology of the CBO framework and the perspective of community empowerment with a case study in Cilacap Regency, Central Java. Primary data was collected by in-depth interviews and focus group discussions, while secondary data was collected by literature review. The data was processed using content analysis techniques. This research found that the activism of FWBM has been manifested in four holistic community empowerment programmes. Through these programmes, ex Indonesian Migrant Workers and their families can improve their quality of life. They can be more empowered, economically independent, and wealthier. However, the FWBM still has limitations in terms of volunteers and financial resources to support sustainable activities.